PELAKSANAAN DISPENSASI KAWIN SETELAH BERLAKUNYA PERATURAN MAHKAMAH AGUNG NOMOR 5 TAHUN 2019 DI PENGADILAN AGAMA NAMLEA: - - afwan, afwan arsad; Toisuta, Hasbollah; Mualim, Much (Jurnal Studi Islam, 2024)
Data from the Registrar’s Office of the Ambon High Religious Court noted that the Namlea Religious Court contributed the highest number of Marriage Dispensation cases in the 2021-2022 period in the Maluku region, even though the enactment of Supreme Court Regulation Number 5 of 2019 was to minimize and reduce the number of underage marriages occurring in Indonesia. Even though the regulations and requirements have been regulated in more detail and detail, the number of Marriage Dispensations is still high in the Namlea Religious Court. Based on these problems, researchers are anxious to find out about several things, including: 1). Knowing how to apply Supreme Court Regulation Number 5 of 2019 in the Namlea Religious Court, so that the Marriage Dispensation is still high. 2). Find out what the judge’s considerations are in accepting and rejecting Marriage Dispensation Applications at the Namlea Religious Court since the enactment of PERMA Number 5 of 2019.This research is field research which uses descriptive qualitative research with a phenomenological approach. The research results it can be concluded that 1). The still high number of dispensations at the Namlea Religious Court is due to the fact that when filing marriage dispensation cases, dispensation applicants are already pregnant. 2). The Namlea Religious Court Judge’s considerations in granting and rejecting the Marriage Dispensation Application took into account “very urgent reasons” as well as Islamic Law Considerations. By granting the Petitioner’s Marriage Dispensation Application, it will close the door to harm and will provide benefits for the Petitioner Keywords: marriage dispensation,Supreme Court Regulation, Namlea